Psychometric Measurement of Fertility-related Quality of Life across Gender in Primary Infertile Couples - Amita Kumari; Afreen Begum H. Itagi; V. Bhargava Reddy Kanchi; Vijayan Sharmila; Satish Pundlik Dipankar (Journal of Human Reproductive Sciences)
Background: Infertility is a crucial global public health issue that affects millions of people of reproductive age. Fertility-related stress can negatively impact infertile couples’ quality of life (QoL). Aims: This study aimed to assess and compare the psychometric properties of fertility QoL between primary infertile couples’ male and female partners. Settings and Design: This cross-sectional study included 114 primary infertile couples visiting the Andrology Laboratory referred from the Gynaecology and Obstetrics Department, AIIMS, Patna. Materials and Methods: Data were collected using the Fertility QoL (FertiQoL) tool, an internationally validated questionnaire to measure the reproductive QoL, demographic information and medical history. The FertiQoL questionnaire responses were recorded and analysed. Statistical Analyses Used: Statistical analyses used were performed using the SPSS 20.0 version. Descriptive statistics, Kolmogorov–Smirnov test, Cronbach’s alpha and Student’s independent t-tests were used. Statistical significance was set at P < 0.05. Results: In our study, the overall estimated Cronbach’s α was 0.83, and males had a significantly better fertility-related QoL in all domains of the FertiQoL, such as emotional (P < 0.000), mind–body (P < 0.000), social (P < 0.004) and tolerability (P < 0.000), except relational and environmental domains, which were lower in them. However, between the groups, the relational domain was significant (0.000) and the environmental domain was non-significant (0.592). Overall, males had a significantly better total core score, total treatment score and overall total FertiQoL score, while females had lower scores. Conclusion: Amongst infertile couples, the reproductive QoL was poorer in females than in males. Our study suggests psychological counselling and mental support for females during infertility management.